Woof : A bowser and birdie novel - Quinn Spencer (U.S.A.: Scholastic press inc., 2015)
There is trouble brewing in the Louisiana swamp - Bowser can smell it. Bowser is very handsome and only slightly slobbery dog, and he can smell lots of things. Like bacon. And rawhide chews. and the